Tax Incentives (Massachausetts : Heath Lexington Books, 1971)
This discussion concerns two principal aspects: the criteria for identifying the tax incentive provisions contained in the federal income tax and other taxes; and the criteria for comparing the use of tax incentives with the use of direct government expenditures.
This book is a compilation of symposium conducted by the Tax Institute of America, between November 20 - 21, 1969
osc 28/06/17
Loans
Keywords: Taxation